2018
DOI: 10.7554/elife.34798
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-based diffusion barrier separates membrane domains enabling the formation of microbiostatic frustrated phagosomes

Abstract: Candida albicans hyphae can reach enormous lengths, precluding their internalization by phagocytes. Nevertheless, macrophages engulf a portion of the hypha, generating incompletely sealed tubular phagosomes. These frustrated phagosomes are stabilized by a thick cuff of F-actin that polymerizes in response to non-canonical activation of integrins by fungal glycan. Despite their continuity, the surface and invaginating phagosomal membranes retain a strikingly distinct lipid composition. PtdIns(4,5)P2 is present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 136 publications
(190 reference statements)
6
42
0
Order By: Relevance
“…These layers corresponded to cuffs made from polymerized actin (Fig. D), similarly to what was previously observed for ‘frustrated phagosomes’ of macrophages being unable to fully ingest hyphae (Strijbis et al, ; Maxson et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These layers corresponded to cuffs made from polymerized actin (Fig. D), similarly to what was previously observed for ‘frustrated phagosomes’ of macrophages being unable to fully ingest hyphae (Strijbis et al, ; Maxson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Fungal hyphae formed by major pathogens like C. albicans or A. fumigatus , in contrast, escape phagocytic predation by pure physical constraints, and call for alternative tools to control fungal growth. Fungistatic mechanisms have been attributed to the formation of neutrophil extracellular traps and frustrated phagosomes of innate immune cells, but these structures were found to be insufficient to kill and eliminate fungal pathogens (Bruns et al, ; Menegazzi et al, ; Maxson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Myosin IE,F,G all connect the membrane to the cytoskeleton, are present at the phagocytic cup and have been shown to participate in target engulfment (Barger et al 2019, Dart et al 2012. Alternatively, the presence of adhesive integrins and podosome-like structures may also contribute to mechano-signaling (Maxson et al 2018, Ostrowski et al 2019. While the FcγR is classically seen as a signaling receptor, comparative reasoning suggests that it might also act as a mechanoreceptor.…”
Section: Discussionmentioning
confidence: 99%
“…LAMP1 accumulation at the frustrated phagosome was previously described in RAW246.7 macrophages spreading on IgG-ovalbumin micro-patterned surfaces and was found to be accompanied by the release of β-hexosaminidase ( 21 ). Very recently, it was also demonstrated that during the frustrated phagocytosis of C. albicans hyphae by RAW macrophages, LAMP1 + vesicles accumulated at the interface with the fungus and in close proximity of the actin cuff, suggesting that complete enclosing of the phagosome is not required for the recruitment of lysosomes to the phagocytic synapse ( 35 ).…”
Section: Discussionmentioning
confidence: 99%